Multislice computer tomography (MSCT) for the optimisation of transcatheter aortic valve implantation (TAVI) - Schultz, Carl J.; de Jaegere, Peter P.T. (SA Heart Journal, 2017)
Transcatheter aortic valve replacement (TAVI) is a novel therapy that is increasingly used to treat patients with severe aortic stenosis at high risk for surgical valve replacement. Patient selection, procedural planning and evaluation all require a detailed analysis of patient anatomy. The role and added value of multislice computer tomography (MSCT) is described as a 3-D imaging modality that enables a comprehensive evaluation of the complex 3-D anatomy of the aortic root, planning of all potential transcatheter access routes and evaluation of prosthesis anatomy interactions post-implantation.